Soluble HLA-G Expression Inversely Correlates With Fetal Microchimerism Levels in Peripheral Blood From Women With Scleroderma - Di Cristofaro, Julie; Karlmark, Karlin R.; Kanaan, Sami B.; Azzouz, Doua F.; El Haddad, Marina; Hubert, Lucas; Farge-Bancel, Dominique; Granel, Brigitte; Harlé, Jean Robert; Hachulla, Eric; Pardoux, Etienne; Roudier, Jean; et al. (Frontiers in Immunology, 2018)
Women with scleroderma (SSc) maintain significantly higher quantities of persisting fetal microchimerism (FMc) from complete or incomplete pregnancies in their peripheral blood compared to healthy women. The non-classical class-I Human Leukocyte Antigen (HLA) molecule HLA-G plays a pivotal role for the implantation and maintenance of pregnancy and has often been investigated in offspring from women with pregnancy complications. However data show that maternal HLA-G polymorphisms as well as maternal soluble HLA-G (sHLA-G) expression could influence pregnancy outcome. Here we aimed to investigate the underlying role of maternal sHLA-G expression and HLA-G polymorphisms on the persistence of FMc. We measured sHLA-G levels by ELISA in plasma samples from 88 healthy women and 74 women with SSc. Male Mc was quantified by DYS14 real-time PCR in blood samples from 58 women who had previously given birth to at least one male child. Furthermore, eight HLA-G 5’URR/3’UTR polymorphisms, previously described as influencing HLA-G expression, were performed on DNA samples from 96 healthy women and 106 women with SSc. Peripheral sHLA-G was at lower concentration in plasma from SSc (76.2 +/- 48.3 IU/mL) compared to healthy women (117.5 +/- 60.1 IU/mL, p<0.0001), independently of clinical subtypes, autoantibody profiles, disease duration or treatments. Moreover sHLA-G levels were inversely correlated to FMc quantities (Spearman correlation, p<0.01). Finally, women with SSc had lower sHLA-G independently of the eight HLA-G 5’URR/3’UTR polymorphisms, although they were statistically more often homozygous than heterozygous for HLA-G polymorphism genotypes -716 (G/T), -201 (G/A), 14bp (ins/del) and +3142 (G/A) than healthy women. In conclusion, women with SSc display less sHLA-G expression independently of the eight HLA-G polymorphisms tested. This decreased production correlates with higher quantities of persisting FMc commonly observed in blood from SSc women. These results shed some lights on the contribution of the maternal HLA-G protein to long-term persistent fetal Mc and initiate new perspectives in this field.